The Goals and Objectives of My School Integrated Information Tools in the Subject (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
In this article, an analysis process was carried out in which the purpose of integrated mediata education in school reading science, in addition to widely popular assignments: “sheep”, “ajrat”, “markila”, “remember”, “re-develop”, “make on a sample basis” tasks, statistical analysis views were explained.